Badanie podobieństwa odległości między obiektami dla dziesięciu par wybranych formuł normalizacyjnych - Pawełek, Barbara (Research of Similarity of Distance between Objects for Ten Pairs of Normalization Transformations, 2008)
The paper presents the measure of similarity of distance between objects. There are given its form for ten pairs of normalization transformations. This measure can find application in the research of conditions which favour receiving similarity or dissimilarity results in comparative analysis into complex economic phenomena with two different normalization transformations.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 190-198